Pengaruh Keragaman Produk Terhadap Pengambilan Keputusan Nasabah dalam Menggunakan Jasa Pegadaian Syariah Ditinjau Dari Etika Bisnis Islam (Studi Pada Pegadaian Syariah Cabang Raden Intan Bandarlampung) - Lutfi Zaimuddin (Dinar Islamic Review, 2021)
The problem of this research is how the influence of product diversity on customer decision-making in using sharia pawnshop services? and What is the view of Islamic business ethics regarding product diversity in sharia pawnshops? The purpose of this study was to determine the effect of product diversity on customer decision-making in using sharia pawnshops and to find out the views of Islamic business ethics about product diversity in sharia pawnshops. This research uses quantitative methods. This research is included in the field research. Sources of data in the form of primary data and secondary data. Data collection techniques consist of observation, interviews, questionnaires, and documentation. The population in this study was 2305 customers and the sample used in this study was 95 customers. The data analysis process uses simple regression analysis with product diversity as the independent variable and decision making as the dependent variable. Based on the results of research conducted by the author, the independent variable simultaneously has a significant influence on the dependent variable. This is evidenced by the Tcount of 13.516 Ttable 1.986 and the probability (sig) turns out to be 0.000 0.05. For the contribution of the product diversity variable in explaining its influence on customer decision-making, it is quite large, namely 66.3%, and the remaining 33.7% is influenced by other variables not found in this study.